Stand your ground laws and homicides - Chandler McClellan; Erdal Tekin (Institute for the Study of Labor (IZA), 2012)
The controversies surrounding Stand Your Ground laws have recently captured the nation's attention. Since 2005, eighteen states have passed laws extending the right to self-defense with no duty to retreat to any place a person has a legal right to be, and several additional states are debating the adoption of similar legislation. Despite the implications that these laws may have for public safety, there has been little empirical investigation of their impact on crime and victimization. In this paper, we use monthly data from the U.S. Vital Statistics to examine how Stand Your Ground laws affect homicides. We identify the impact of these laws by exploiting variation in the implementation of these laws across states. Our results indicate that Stand Your Ground laws are associated with a significant increase in the number of homicides among whites, especially white males. According to our estimates, between 4.4 and 7.4 additional white males are killed each month as a result of these laws. We find no evidence to suggest that these laws increase homicides among blacks. Our results are robust to a number of specifications and unlikely to be driven entirely by the killings of assailants. Taken together, our findings raise serious doubts against the argument that Stand Your Ground laws make America safer.
Keywords: I1; K14; K42; 330; homicide; stand your ground; castle doctrine; guns; crime; Waffenrecht; Privatrecht; Kriminalität; USA